Sheet and container

By using a resin composition with high polar functional group content on the polypropylene finished product and combining with a hot melt adhesive coating, the problem of insufficient hot melt adhesive strength under low temperature conditions is solved, and an efficient bonding effect is achieved.

JP2025044610APending Publication Date: 2025-04-02KOBAYASHI & CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023152294
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-20
Publication Date
2025-04-02

AI Technical Summary

Technical Problem

The prior art is difficult to effectively paste the hot melt adhesive coating onto the finished polypropylene (PP) products under low temperature conditions, and the bonding strength between the hot melt adhesive and polypropylene is insufficient, resulting in poor adhesion when the hot melt adhesive is peeled off.

Method used

A resin composition containing polar functional groups is used to prepare a resin composition for the finished polypropylene product, and a hot melt adhesive coating is added to the resin composition. By combining the hot melt adhesive coating with the resin composition, the bonding strength between the finished polypropylene product and the hot melt adhesive is improved.

Benefits of technology

Under low temperature conditions, the bonding strength between hot melt adhesive and polypropylene products is significantly improved, and the poor adhesion phenomenon during hot melt adhesive peeling is reduced, ensuring good adhesion performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025044610000002
    Figure 2025044610000002
  • Figure 2025044610000003
    Figure 2025044610000003
  • Figure 2025044610000004
    Figure 2025044610000004
Patent Text Reader

Abstract

To provide a container in which a film applied with a hot-melt composition can be heat-sealed at a sufficient joining strength (removal strength) to a container body formed of polypropylene resin and, even under a low temperature state, the stick-slip phenomenon can be suppressed when the heat-sealed film is removed from the container body.SOLUTION: The present invention provides a container comprising a container body that is formed of a resin composition containing a polypropylene resin and a resin containing a polar functional group and a lid material that is joined to the container body in a manner sealing an opening of the container body.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present technology relates to a sheet and a container. In particular, the present technology relates to a sheet and a container used in the food industry, particularly to a sheet and a container used for frozen desserts such as ice cream. More particularly, the present technology relates to a sheet and a container such as a drink cup stored in a freezer environment. [Background technology]

[0002] Containers for storing frozen desserts such as ice cream generally use either a top seal or a fitting lid to seal the container body so that the contents stored in the container do not leak. In light of recent environmental concerns, the top seal type, which seals the container body using a top seal, is becoming more commonly used than the fitting lid type, because it uses less plastic than the fitting lid type, which seals the container body using a fitting lid. As the top seal type, a film laminated with a low melting point resin such as low density polyethylene, low molecular weight polyester, ethylene-unsaturated ester copolymer, or a film coated with a hot melt composition only on the adhesive surface with the container body is used. When the opening of the container body is sealed with a film laminated with a low melting point resin, plastic residues may remain on the peeled surface of the container body when the film is peeled off from the container body, so a film coated with a hot melt composition is used as the lid material for many containers. For example, as shown in Patent Document 1, a technology has been proposed in which the opening of a container body formed from PET resin is sealed with a film coated with a hot melt composition. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2017-149850 A Summary of the Invention [Problem to be solved by the invention]

[0004] Conventionally, a film coated with a hot melt composition is used to heat seal a container body made of polystyrene (PS) resin, which is amorphous, has a low softening point, and has polarity, at 120°C or less. Due to a decrease in the supply of raw materials and a rise in the price of raw materials, it is desired to switch to a container body made of polypropylene (PP) resin, which is less expensive than a container body made of polystyrene (PS) resin. However, even if a film coated with a hot melt composition capable of heat sealing is used to heat seal a container body made of polypropylene (PP) resin at 120°C or less, there is a problem that the adhesive strength between the polypropylene (PP) resin, which has a high melting point and is non-polar, and the hot melt composition is low, and the adhesive strength between the hot melt composition and the polypropylene (PP) resin cannot reach the required characteristics.

[0005] Furthermore, when the heat-sealed film is peeled off from the container body under low-temperature conditions in which frozen desserts are stored, there is an issue that a stick-slip phenomenon occurs, in which a strong resistance and noise are felt and the adhesive strength alternates between relatively strong and weak.

[0006] One object of the present invention is to provide a container in which a film coated with a hot melt composition can be heat-sealed to a container body formed from a polypropylene resin with sufficient adhesive strength (peel strength), and in which the stick-slip phenomenon can be suppressed when the heat-sealed film is peeled from the container body even under low temperature conditions. [Means for solving the problem]

[0007] This technology is Polypropylene resin, A container body formed from a resin composition including a resin having a polar functional group; A lid material joined to the container body so as to seal the opening of the container body; A container having: The polar functional group can be an oxygen-containing group. The content of the polypropylene resin may be 30 to 99% by mass based on the mass of the resin composition. The content of the resin containing a polar functional group may be 1 to 70% by mass based on the mass of the resin composition. The lid material may have a sealant layer on the surface that is to be joined to the resin composition. The sealant layer may comprise a hot melt composition. The hot melt composition may comprise an ethylene-vinyl acetate copolymer resin. When the container body and the lid material to which the hot melt composition is applied are attached to each other and the lid material is peeled off from the container body at 25° C., cohesive failure may occur in the hot melt composition. When the container body and the lid material to which the hot melt composition is applied are bonded together and the lid material is peeled off from the container body at 0° C., cohesive failure may occur in the hot melt composition. In addition, this technology: Polypropylene resin, and a resin containing a polar functional group. In addition, this technology: A base layer; A seal layer disposed on one surface side of the base layer; A sheet having The sealing layer is made of a polypropylene resin, and a resin including a polar functional group; The present invention also provides a sheet, in which the base layer is formed from a resin composition that is the same as or different from the first resin composition. When a hot melt tape having a hot melt composition applied thereto is adhered to the sheet and the hot melt tape is peeled from the sheet at 25° C., the peel strength may be 0.5 kgf / 15 mm or more. When a hot melt tape having a hot melt composition applied thereto is adhered to the sheet and the hot melt tape is peeled from the sheet at 0° C., the peel strength may be 0.5 kgf / 15 mm or more. Effect of the Invention

[0008] This technology can provide a container in which a film coated with a hot melt adhesive can be heat-sealed to a container body formed from polypropylene resin with sufficient adhesive strength (peel strength), and in which the stick-slip phenomenon can be suppressed when the heat-sealed film is peeled off from the container body, even at low temperatures. [Brief description of the drawings]

[0009] [Figure 1] FIG. 2 is a perspective view showing an example of a container according to the first embodiment. [Diagram 2] FIG. 2 is a perspective view showing an example of a container body according to the first embodiment. [Diagram 3] FIG. 2 is a cross-sectional view showing the bonded state of a lid material and a single-layer sheet before the lid material is peeled off from the single-layer sheet. [Figure 4] FIG. 1 is a diagram showing how peeling due to cohesive failure occurs in the sealant layer (hot melt composition) of a lid material when the lid material is peeled off from a single-layer sheet. [Diagram 5] FIG. 1 is a diagram showing how peeling due to cohesive failure occurs in the sealant layer (hot melt composition) of a lid material when the lid material is peeled off from a single-layer sheet. [Figure 6] FIG. 13 is a diagram showing how peeling due to cohesive failure occurs near the interface between the sealant layer of the lid material and the seal layer of the monolayer sheet when the lid material is peeled off from the monolayer sheet. [Figure 7] FIG. 11 is a cross-sectional view of an example of a multilayer sheet according to a third embodiment. [Figure 8] FIG. 11 is a cross-sectional view of another example of the multilayer sheet according to the third embodiment. [Figure 9] FIG. 11 is a schematic diagram showing an example of a multilayer co-extrusion molding machine used in the manufacturing method of a multilayer sheet according to a third embodiment. [Figure 10] 1 is a photograph showing how the stick-slip phenomenon does not occur on the peeled surface during peeling. [Figure 11]1 is a photograph showing a state in which a slight stick-slip phenomenon occurs on the peeled surface during peeling. [Figure 12] 1 is a photograph showing the state in which the stick-slip phenomenon occurs on the peeled surface during peeling. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Preferred embodiments for carrying out the present technology will be described below. Note that the embodiments described below are representative embodiments of the present technology, and the scope of the present technology is not limited to these embodiments.

[0011] This technology will be described in the following order. 1. First embodiment (example of container) (1) Container composition (2) Manufacturing method of container 2. Second embodiment (example of single layer sheet) (1) Seat configuration (2) Seat manufacturing method (3) Physical properties of the sheet 3. Third embodiment (example of multilayer sheet) (1) Structure of the multi-layer sheet (2) Manufacturing method of multilayer sheet (3) Physical properties of multilayer sheets 4. Working Example

[0012] 1. First embodiment (example of container)

[0013] (1) Container composition

[0014] Hereinafter, the configuration of the container according to this embodiment will be described with reference to the drawings. In this specification, "the direction perpendicular to an object (e.g., a container, etc.) placed on a horizontal plane with the surface on which food, etc. is placed facing upward" is referred to as "thickness direction," and "any direction within a plane perpendicular to the thickness direction" is referred to as "planar direction." Also, "viewing an object (e.g., a container, etc.) placed on a horizontal plane with the surface on which food, etc. is placed facing upward in the thickness direction from above in the vertical direction" is referred to as "planar view." Furthermore, of the two surfaces of a container that face each other in the thickness direction, the surface on which food, etc. is placed is referred to as the "inner surface," and the other surface opposite is referred to as the "outer surface."

[0015] The container of this embodiment is composed of a container body and a lid. The container body is formed from a resin composition and includes, for example, a bottom portion, a side portion extending upward from the periphery of the bottom portion, and an opening surrounded by the upper end of the side portion. The container body may further include, for example, a flange portion formed by extending outward from the opening. The lid closes the opening of the container body.

[0016] In the container body, the shape of the bottom surface and the opening may be, for example, a circle, an ellipse, a polygon, or a substantially polygonal shape, but is not particularly limited. The shape of the bottom surface and the opening may be the same or different. The side surface may be perpendicular to the bottom surface, and may be tapered or inverted tapered. The shape of the container body having the bottom surface, the side surface, and the opening may be, for example, a bottomed cylindrical shape or a bottomed inverted truncated cone shape, but is not particularly limited.

[0017] Hereinafter, the container of this embodiment will be described with reference to the drawings.

[0018] FIG. 1 is a perspective view of an example of a container of this embodiment (hereinafter, also referred to as "container 10"). As shown in FIG. 1, the container 10 is composed of a container body 11 and a lid member 12. FIG. 2 is a perspective view of the container body 11 showing a state in which the lid member 12 is separated from the container 10 of this embodiment. As shown in FIG. 2, the container body 11 includes a bottom surface portion 15, a container body side surface portion 16 that extends and spreads upward from the outer edge of the bottom surface portion 15, and a flange portion 14 that extends outward from the upper end of the container body side surface portion 16. Also, as shown in FIG. 2, the container body 11 includes an opening portion 13 surrounded by the upper end of the container body side surface portion 16.

[0019] [Container body]

[0020] The container body of the present embodiment is formed from a resin composition containing a polypropylene resin and a resin containing a polar functional group. The resin composition will be described below.

[0021] [Resin composition]

[0022] The resin composition forming the container body of this embodiment contains a polypropylene resin and a resin containing a polar functional group.

[0023] (Polypropylene resin)

[0024] In this embodiment, the polypropylene resin contained in the resin composition is not particularly limited. Examples of such polypropylene resins include homopolymer polypropylene resins, random copolymer or block copolymer polypropylene resins (e.g., ethylene-propylene copolymers, etc.), or combinations of these resins. In this embodiment, random copolymer polypropylene resins are preferred. In this embodiment, only one type of polypropylene resin may be used, or two or more types of polypropylene resins may be used in combination.

[0025] In the present embodiment, the polypropylene resin contained in the resin composition is not particularly limited. From the viewpoint of peel strength, the polypropylene resin may have a melting point of preferably 170° C. or less, more preferably 160° C. or less, and even more preferably 150° C. or less. From the viewpoint of moldability, the polypropylene resin may have an MFR of preferably 0.1 to 20.0 g / 10 min, more preferably 0.3 to 15.0 g / 10 min, and even more preferably 0.5 to 10.0 g / 10 min, measured in accordance with JIS-K-7210 (1995) condition M (230° C., 2.16 kgf).

[0026] Commercially available polypropylene resins can also be used as the polypropylene resin. Examples of such polypropylene resins include "Novatec (registered trademark) FY6" manufactured by Japan Polypropylene Corporation, "Novatec (registered trademark) EG6D" manufactured by Japan Polypropylene Corporation, "Wintech (registered trademark) WFX6" manufactured by Japan Polypropylene Corporation, "PL400A" manufactured by SunAllomer Corporation, "PS320M" manufactured by SunAllomer Corporation, "Qualia (registered trademark) CS356M" manufactured by SunAllomer Corporation, "E111G" manufactured by Prime Polymer Corporation, "E330GV" manufactured by Prime Polymer Corporation, "E701G" manufactured by Prime Polymer Corporation, "Noblen (registered trademark) D101" manufactured by Sumitomo Chemical Co., Ltd., and "Noblen (registered trademark) FL6632G" manufactured by Sumitomo Chemical Co., Ltd.

[0027] From the viewpoint of mechanical strength, the content of the polypropylene resin is preferably 30% by mass or more and 99% by mass or less, more preferably 35% by mass or more and 96% by mass or less, even more preferably 40% by mass or more and 93% by mass or less, and even more preferably 45% by mass or more and 90% by mass or less, relative to the mass of the resin composition.

[0028] (Resin containing polar functional groups)

[0029] In this embodiment, the resin containing a polar functional group contained in the resin composition is a component added to improve the adhesive strength between the polypropylene resin and the hot melt composition and to suppress the occurrence of stick-slip when peeled off under low temperature conditions. The polar functional group is a functional group having polarity, and examples thereof include an epoxy group, a hydroxyl group, an amino group, a nitro group, a carboxyl group, a formyl group, a nitrile group, and a sulfonic acid group. Such a polar functional group may preferably be an oxygen-containing group. Examples of the oxygen-containing group include a carboxyl group. Examples of the resin containing an oxygen-containing group include a copolymer or an ionomer containing at least ethylene and a polar functional group-containing monomer. From the viewpoint of adhesive strength, the content of the resin containing a polar functional group is preferably 1 mass% or more and 70 mass% or less, more preferably 4 mass% or more and 65 mass% or less, even more preferably 7 mass% or more and 60 mass% or less, and even more preferably 10 mass% or more and 55 mass% or less, relative to the mass of the resin composition. Hereinafter, the copolymer containing at least ethylene and a polar functional group-containing monomer will be described.

[0030] (Copolymer containing at least ethylene and a monomer containing a polar functional group)

[0031] In this embodiment, the copolymer containing at least ethylene and a polar functional group-containing monomer contained in the resin composition may be a block copolymer or a random copolymer. The ethylene unit contained in the copolymer containing at least ethylene and a polar functional group-containing monomer may be a low density polyethylene (LDPE) having a large number of branched chains or a linear low density polyethylene (LLDPE). As the ethylene, ethylene derived from a petroleum raw material or ethylene derived from a non-petroleum raw material such as a plant raw material may be used as necessary.

[0032] The polar functional group-containing monomer means a monomer having at least one functional group other than the group involved in copolymerization with ethylene. The functional group of the polar functional group-containing monomer includes an ether group, a hydroxyl group, an ester group, a carbonyl group, an amino group, an amide group, etc. From the viewpoint of improving the adhesive strength to the hot melt composition, it is preferable to use a polar functional group-containing monomer having an ester group.

[0033] Non-limiting examples of polar functional group-containing monomers include vinyl acetate, acrylic acid, acrylic acid esters such as methyl acrylate and ethyl acrylate, methacrylic acid esters such as methyl methacrylate and ethyl methacrylate, and copolymers of the polar functional groups and maleic anhydride described above. The use of methyl acrylate is preferred from the viewpoint of improving the adhesive strength with the hot melt composition and suppressing stick-slip in a low-temperature environment. Only one type of polar functional group-containing monomer may be used in the copolymer, or two or more types of monomers may be used in combination. When two or more kinds of polar functional group-containing monomers are used in combination, the ratio of the amounts of each can be determined within any range depending on the desired properties of the resin composition, and is not particularly limited.

[0034] The copolymer containing at least ethylene and a polar functional group-containing monomer may be a copolymer containing a monomer other than ethylene and a polar functional group-containing monomer. Non-limiting examples of such monomers include those having the structural formula: CH2=CHR 18 Examples of the α-olefins include those having 3 to 20 carbon atoms, represented by the formula: 18is a hydrocarbon group having 1 to 18 carbon atoms, which may have a linear structure or may have a branched structure). The number of carbon atoms of the α-olefin is more preferably 3 to 12. More specifically, examples thereof include propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 3-methyl-1-butene, and 4-methyl-1-pentene. When a monomer other than ethylene and the polar functional group-containing monomer is further contained, the content of such a monomer is preferably in the range of 1% by weight to 30% by weight, more preferably in the range of 3% by weight to 25% by weight, based on the entire copolymer. By setting the content within this range, it is possible to introduce physical properties due to the added monomer.

[0035] Examples of copolymers containing at least ethylene and a polar functional group-containing monomer include copolymers of ethylene and a polar group-containing monomer polymerized by a metal catalyst such as a metallocene catalyst, and ethylene-methyl acrylate copolymers (EMA), ethylene-vinyl acetate copolymers (EVA), ethylene-methyl methacrylate copolymers (EMMA), ethylene-ethyl acrylate copolymers (EEA), ethylene-methacrylic acid copolymers (EMAA), ethylene-acrylic acid copolymers (EAA), ethylene-acrylic acid ester-maleic anhydride ternary copolymers, and ethylene-vinyl acetate-maleic anhydride ternary copolymers, which are polymerized using an organic peroxide as a reaction initiator.

[0036] In the present invention, from the viewpoints of adhesive strength to a hot melt composition and suppression of stick-slip, the copolymer is preferably an ethylene-methyl acrylate copolymer (EMA), an ethylene-ethyl acrylate copolymer (EEA) or an ethylene-methyl methacrylate copolymer (EMMA), and more preferably an ethylene-methyl acrylate copolymer (EMA).

[0037] The amount of ethylene and the polar functional group-containing monomer in the copolymer is preferably 5% by mass or more, more preferably 8% by mass or more, and even more preferably 12% by mass or more, based on the total amount of the copolymer. The amount of the polar functional group-containing monomer can be controlled by adjusting the mixing ratio of each monomer in the copolymer preparation process.

[0038] From the viewpoint of peel strength, the copolymer may have a melting point of preferably 120° C. or lower, more preferably 110° C. or lower, and even more preferably 100° C. or lower.

[0039] From the viewpoint of moldability, the copolymer may have a melt flow rate (MFR) measured in accordance with the conditions of JIS-K-7210 (1999) (190°C, 2.16 kgf) of preferably 0.1 to 20.0 g / 10 min, more preferably 0.3 to 15.0 g / 10 min, and even more preferably 0.5 to 10.0 g / 10 min.

[0040] The copolymer may be a commercially available product, or may be produced using the monomers described above. Methods of copolymerization using a metal catalyst such as a metallocene catalyst, or a copolymerization using an organic peroxide as a reaction initiator are known to those skilled in the art.

[0041] Commercially available products that can be used as the copolymer include, for example, "REXPEARL EMA" manufactured by Japan Polyethylene Corporation as an ethylene-methyl acrylate copolymer (EMA), "REXPEARL EEA" manufactured by Japan Polyethylene Corporation as an ethylene-ethyl acrylate copolymer (EEA), and "Acryft" manufactured by Sumitomo Chemical Co., Ltd. as an ethylene-methyl methacrylate copolymer (EMMA).

[0042] (Ionomer)

[0043] In this embodiment, the ionomer contained in the resin composition refers to a compound in which at least a part of the acidic groups (e.g., carboxy groups) in a copolymer containing at least one selected from the group consisting of an ethylene-unsaturated carboxylic acid copolymer and an ethylene-unsaturated carboxylic acid-unsaturated carboxylic acid ester copolymer are neutralized with a metal ion. In this specification, the ionomer contained in the resin composition may be a copolymer selected from an ethylene-unsaturated carboxylic acid copolymer or an ethylene-unsaturated carboxylic acid-unsaturated carboxylic acid ester copolymer (hereinafter collectively referred to as "specific copolymers") in which the acidic groups are neutralized with a metal ion with a neutralization degree of 20% or more and 80% or less. As such metal ions, zinc ions, sodium ions, etc. are preferred. In addition to ethylene derived from petroleum raw materials, ethylene derived from non-petroleum raw materials such as plant raw materials can be used as the ethylene. The specific copolymer constituting the ionomer will be described below.

[0044] (Ionomer of ethylene-unsaturated carboxylic acid copolymer)

[0045] The ethylene-unsaturated carboxylic acid copolymer (base polymer) capable of forming an ionomer is a copolymer obtained by copolymerizing at least ethylene and an unsaturated carboxylic acid, and has a structural unit derived from ethylene and a structural unit derived from an unsaturated carboxylic acid. Note that the ethylene-unsaturated carboxylic acid copolymer in this specification may contain a structural unit derived from another monomer as described later, but when it contains a structural unit derived from an unsaturated carboxylic acid ester as a structural unit derived from another monomer, it is included in the "ethylene-unsaturated carboxylic acid-unsaturated carboxylic acid ester copolymer".

[0046] The ethylene-unsaturated carboxylic acid copolymer may be any of a block copolymer, a random copolymer, and a graft copolymer. From the viewpoint of industrial availability, the ethylene-unsaturated carboxylic acid copolymer is preferably a random copolymer.

[0047] In the ethylene-unsaturated carboxylic acid copolymer, examples of the constituent units derived from the unsaturated carboxylic acid include constituent units derived from acrylic acid, methacrylic acid, fumaric acid, maleic acid, etc. Among these, the constituent units derived from the unsaturated carboxylic acid are preferably constituent units derived from acrylic acid or methacrylic acid, and more preferably constituent units derived from methacrylic acid.

[0048] A preferred specific example of the ethylene-unsaturated carboxylic acid copolymer is an ethylene-(meth)acrylic acid copolymer.

[0049] The ethylene-unsaturated carboxylic acid-unsaturated carboxylic acid ester copolymer (base polymer) capable of forming an ionomer is a copolymer obtained by copolymerizing at least ethylene, an unsaturated carboxylic acid, and an unsaturated carboxylic acid ester, and has structural units derived from ethylene, structural units derived from unsaturated carboxylic acid, and structural units derived from unsaturated carboxylic acid ester.

[0050] The ethylene-unsaturated carboxylic acid-unsaturated carboxylic acid ester copolymer may be any one of a block copolymer, a random copolymer, and a graft copolymer. From the viewpoint of industrial availability, the ethylene-unsaturated carboxylic acid-unsaturated carboxylic acid ester copolymer is preferably a random copolymer.

[0051] In the ethylene-unsaturated carboxylic acid-unsaturated carboxylic acid ester copolymer, examples of the constituent unit derived from the unsaturated carboxylic acid include constituent units derived from acrylic acid, methacrylic acid, fumaric acid, maleic acid, etc. Among these, the constituent unit derived from the unsaturated carboxylic acid is preferably a constituent unit derived from acrylic acid or methacrylic acid, and more preferably a constituent unit derived from methacrylic acid.

[0052] The unsaturated carboxylic acid ester forming the structural unit derived from the unsaturated carboxylic acid ester in the ethylene-unsaturated carboxylic acid-unsaturated carboxylic acid ester copolymer is not particularly limited as long as it is copolymerizable with ethylene and the unsaturated carboxylic acid, and examples thereof include unsaturated carboxylic acid alkyl esters. Examples of unsaturated carboxylate alkyl esters include unsaturated carboxylate alkyl esters having 1 to 12 carbon atoms, such as acrylate alkyl esters such as methyl acrylate, ethyl acrylate, isobutyl acrylate, n-butyl acrylate, and isooctyl acrylate; methacrylate alkyl esters such as methyl methacrylate, ethyl methacrylate, and isobutyl methacrylate; and maleate alkyl esters such as dimethyl maleate and diethyl maleate.

[0053] Among these, the unsaturated carboxylic acid alkyl ester is preferably an alkyl ester of acrylic acid or methacrylic acid such as methyl acrylate, ethyl acrylate, isopropyl acrylate, isobutyl acrylate, n-butyl acrylate, methyl methacrylate, ethyl methacrylate, isobutyl methacrylate, n-butyl methacrylate, or isooctyl methacrylate, and more preferably a lower alkyl ester of acrylic acid or methacrylic acid (an alkyl ester having 2 to 5 carbon atoms).

[0054] Preferred specific examples of the ethylene-unsaturated carboxylic acid-unsaturated carboxylic acid ester copolymer include ethylene-(meth)acrylic acid-(meth)acrylic acid ester copolymers (e.g., ethylene-(meth)acrylic acid-methyl acrylate copolymer, ethylene-(meth)acrylic acid-ethyl acrylate copolymer, ethylene-(meth)acrylic acid-butyl acrylate copolymer, etc.).

[0055] The specific copolymer may contain, in addition to the above-mentioned structural units, structural units derived from other monomers (hereinafter also referred to as "other structural units"). Examples of other structural units include structural units derived from unsaturated hydrocarbons (e.g., propylene, butene, 1,3-butadiene, pentene, 1,3-pentadiene, 1-hexene, etc.), vinyl esters (e.g., vinyl acetate, vinyl propionate, etc.), oxides such as vinyl sulfate and vinyl nitrate, halogen compounds (e.g., vinyl chloride, vinyl fluoride, etc.), vinyl group-containing primary and secondary amine compounds, carbon monoxide, sulfur dioxide, etc.

[0056] (Degree of neutralization)

[0057] From the viewpoints of elastic modulus and moldability, the degree of neutralization of the ionomer is preferably 20% or more and 80% or less, more preferably 25% or more and 75% or less, and even more preferably 30% or more and 70% or less. In this specification, the "degree of neutralization" refers to the blending ratio (mol %) of metal ions relative to the number of moles of acidic groups, particularly carboxyl groups, contained in the specific copolymer (base polymer).

[0058] The ionomer may contain two or more specific copolymers, for example, an ethylene-unsaturated carboxylic acid copolymer and an ethylene-unsaturated carboxylic acid-unsaturated carboxylic acid ester copolymer.

[0059] (MFR)

[0060] The melt flow rate (MFR: measured in accordance with JIS K7210-1999, 190°C, 2160 g load) of the ionomer is preferably 0.1 g / 10 min or more and 30 g / 10 min or less, and more preferably 0.5 g / 10 min or more and 20 g / 10 min or less, from the viewpoint of molding processability, etc.

[0061] As the ionomer, a commercially available product may be used, for example, Himilan (registered trademark) series manufactured by DuPont-Mitsui Polychemicals Co., Ltd.

[0062] (Additives)

[0063] The resin composition forming the container body of the present embodiment may further contain additives, such as antioxidants, heat stabilizers, light stabilizers, ultraviolet absorbers, lubricants, antistatic agents, flame retardants, pigments, dyes, dispersants, plasticizers, compatibilizers, deodorizers, and nucleating agents.

[0064] The additives may be used alone or in combination of two or more kinds.

[0065] When additives are blended, the blending amount of the additives is preferably 0.1 mass % or more and 20 mass % or less, more preferably 0.3 mass % or more and 15 mass % or less, and even more preferably 0.5 mass % or more and 10 mass % or less, relative to the mass of the resin composition.

[0066] [Lid material]

[0067] The lid material of this embodiment has a sealant layer formed by applying a hot melt composition to one side of the substrate. The lid material has a sealant layer on the side of the container body that is bonded to the resin composition. In this embodiment, the substrate may be a laminate of at least two or more selected from the group consisting of resin film, paper, and aluminum film (aluminum foil). For example, the resin film may be a resin film formed from a resin such as a polyester resin such as polyethylene terephthalate, a polycarbonate resin, a polyarylate resin, an acrylic resin, a polyphenylene sulfide resin, a polystyrene resin, a vinyl resin, a vinyl chloride resin, a polyimide resin, a polyamide resin, an epoxy resin, a polyolefin resin such as polyethylene, polypropylene, or polyorbornene. The film may also be a vapor deposition film of these films, and examples of the film include a metal vapor deposition film in which a metal such as aluminum is vapor deposited, and a transparent vapor deposition film in which alumina, silicon oxide, or the like is vapor deposited. Preferred are polyethylene film, polypropylene film, polyethylene terephthalate film, and vapor-deposited films thereof, and preferred vapor-deposited films are metal-deposited polyethylene terephthalate film, transparent vapor-deposited polypropylene film, and transparent vapor-deposited polyethylene terephthalate film. The lid material may further be laminated with nonwoven fabric, woven fabric, cloth, glass, etc.

[0068] The laminate structure of the substrate is not particularly limited, but preferred examples include "paper / polyethylene," "polyethylene terephthalate / paper / polyethylene," "polyethylene terephthalate / aluminum foil / polyethylene," and "polyethylene terephthalate / paper / polyethylene terephthalate / polyethylene." Furthermore, if necessary, the surface of the substrate may be subjected to a treatment for improving adhesion, such as a corona discharge treatment, a plasma treatment, a blast treatment, or a chemical etching treatment, an antistatic treatment, a coloring treatment, or the like. There is no particular limitation on the thickness of the substrate, but it is preferably 1 to 300 μm.

[0069] (Hot melt composition)

[0070] The hot melt composition used in the lid material of the present embodiment is not particularly limited, but may contain, for example, an ethylene copolymer, a tackifier resin, a wax, and the like.

[0071] <Ethylene-based copolymer>

[0072] Examples of ethylene-based copolymers contained in the hot melt composition include ethylene-unsaturated ester copolymers. Such ethylene-unsaturated ester copolymers are one of the main components in the hot melt composition, and mainly play a role in imparting adhesive strength and cohesive strength. The ethylene-unsaturated ester copolymer is a copolymer of ethylene and an unsaturated ester monomer, and examples of the unsaturated ester monomer include (meth)acrylic acid alkyl esters such as methyl acrylate, ethyl acrylate, isobutyl acrylate, n-butyl acrylate, isooctyl acrylate, methyl methacrylate, and isobutyl methacrylate, unsaturated carboxylic acid alkyl esters such as dimethyl maleate and diethyl maleate, and carboxylic acid vinyl esters such as vinyl acetate and vinyl propionate.

[0073] In the ethylene-unsaturated ester copolymer, the unsaturated ester monomer may be used alone or in combination of two or more. As the unsaturated ester monomer, vinyl acetate and methyl methacrylate are preferable, and vinyl acetate is more preferable. The ethylene-unsaturated ester copolymer may be used alone or in combination of two or more.

[0074] <Tackifier resin>

[0075] Examples of tackifying resins contained in the hot melt composition include phenolic resins, modified phenolic resins, xylene phenolic resins, xylene resins, coumarone-indene resins, alkyl phenolic resins, terpene (α-pinene, β-pinene) resins, terpene phenolic resins, rosin, rosin derivatives (hydrogenated rosin, disproportionated rosin, polymerized rosin, rosin esters (esterified rosins such as alcohol, glycerin, pentaerythritol, etc.)), aliphatic (C5) petroleum resins, aromatic (C9) petroleum resins, copolymer (C5 / C9) petroleum resins, alicyclic petroleum resins (hydrogenated or DCPD petroleum resins), and low molecular weight polystyrene resins. Among these, rosin-based resins such as rosin, rosin derivatives (hydrogenated rosin, disproportionated rosin, polymerized rosin, rosin esters (esterified rosins such as alcohol, glycerin, pentaerythritol, etc.)), petroleum-based resins such as aliphatic (C5) petroleum resins, aromatic (C9) petroleum resins, copolymer (C5 / C9) petroleum resins, and alicyclic petroleum resins (hydrogenated or DCPD petroleum resins), and styrene-based resins such as low molecular weight polystyrene resins are preferably used, and more preferably rosin-based resins and petroleum-based resins, and rosin-based resins and petroleum-based resins may be used in combination. As the petroleum-based resin, alicyclic petroleum resins are preferred. The tackifier resin may be used alone or in combination of two or more kinds.

[0076] The softening point of the tackifier resin is preferably in the range of 60 to 160° C., more preferably in the range of 70 to 150° C., and even more preferably in the range of 80 to 140° C. When the softening point is within the above range, the heat resistance is good.

[0077] <Wax>

[0078] Examples of waxes contained in the hot melt composition include carnauba wax, candelilla wax, montan wax, paraffin wax, micro wax, Fischer-Tropsch wax, polyethylene wax, polypropylene wax, acid-modified products of these waxes, special monomer-modified products, ethylene-acrylic acid copolymer wax, ethylene-methacrylic acid copolymer wax, etc. These may be used alone or in combination of two or more kinds. Paraffin wax, polyethylene wax and modified products thereof, and Fischer-Tropsch wax are preferably used, and polyethylene wax and modified products thereof are more preferably used.

[0079] <Other ingredients>

[0080] The hot melt composition may contain, as optional components, antioxidants, silane coupling agents, antiblocking agents, hydrophobic oxide fine particles, etc. These other components may be used alone or in combination of two or more.

[0081] The hot melt composition can be obtained by mixing the above components by a known method. For example, a hot melt composition of the heat melting type can be obtained by heating and mixing using a melting kettle equipped with a roll, a Banbury mixer, a kneader, or a stirrer, or a single-screw or twin-screw extruder. Also, for example, a solvent-type hot melt composition can be obtained by dissolving the components in a known solvent and stirring and mixing.

[0082] The method of manufacturing the lid material is not particularly limited, and the lid material can be manufactured using a known manufacturing method. The method of applying the hot melt composition to the substrate is not particularly limited, and generally known contact coating and non-contact coating are used. Contact coating is a coating method in which a sprayer is brought into contact with the substrate when the hot melt composition is applied to the substrate. Non-contact coating is a coating method in which a sprayer is not brought into contact with the substrate when the hot melt composition is applied to the substrate. Examples of contact coating methods include slot coater coating, gravure coater coating, and roll coater coating, and examples of non-contact coating methods include spiral coating, which can be applied in a spiral shape, omega coating, which can be applied in a wavy shape, control seam coating, slot spray coating, which can be applied in a planar shape, curtain spray coating, dot coating, which can be applied in a dotted shape, and bead coating, which can be applied in a linear shape. The thickness of the sealant layer formed by applying the hot melt composition is preferably 1 to 100 μm. The sealant layer can also be crosslinked by heating or ultraviolet irradiation.

[0083] (2) Manufacturing method of container

[0084] A method for manufacturing a container according to this embodiment will now be described. The method for manufacturing a container according to this embodiment includes a resin composition preparation step of mixing a polypropylene resin and a resin containing a polar functional group to prepare a resin composition, a sheet molding step of extruding the resin composition to mold a sheet, and a container body molding step of molding a container body from the sheet. Each step will be described below.

[0085] [Resin composition preparation process]

[0086] In the resin composition preparation step, the polypropylene resin and the resin containing a polar functional group are mixed by heating, preferably at 270°C or less. In this step, raw materials such as the polypropylene resin and the resin containing a polar functional group may be mixed first. After the raw materials are mixed, the mixed raw materials may be heated and kneaded. In the above step, the polypropylene resin and the resin containing a polar functional group may be heated to a temperature at which the polypropylene resin and the resin containing a polar functional group can be melted. The temperature may be appropriately selected by a person skilled in the art depending on the type and content of the resin containing a polar functional group used.

[0087] In the above step, for example, when the resin containing a polar functional group is an ethylene-methyl acrylate copolymer (EMA), the kneading may be performed at a temperature of preferably 160° C. or higher, more preferably 175° C. or higher, and even more preferably 190° C. or higher. In addition, the kneading may be performed at a temperature of preferably 270° C. or lower, more preferably 260° C. or lower, and even more preferably 250° C. or lower.

[0088] In the above step, for example, when the resin containing a polar functional group is an ethylene-vinyl acetate copolymer (EVA), the kneading may be performed at a temperature of preferably 160° C. or higher, more preferably 175° C. or higher, and even more preferably 190° C. or higher. In addition, the kneading may be performed at a temperature of preferably 250° C. or lower, more preferably 240° C. or lower, and even more preferably 230° C. or lower.

[0089] In the above step, for example, when the resin containing a polar functional group is an ionomer, the kneading may be performed at a temperature of preferably 160° C. or higher, more preferably 175° C. or higher, and even more preferably 190° C. or higher. In addition, the kneading may be performed at a temperature of preferably 270° C. or lower, more preferably 260° C. or lower, and even more preferably 250° C. or lower.

[0090] In the above step, for example, when the resin containing a polar functional group is an ethylene-methyl methacrylate copolymer (EMMA), the kneading may be performed at a temperature of preferably 160° C. or higher, more preferably 175° C. or higher, and even more preferably 190° C. or higher. In addition, the kneading may be performed at a temperature of preferably 270° C. or lower, more preferably 260° C. or lower, and even more preferably 250° C. or lower.

[0091] In the above step, for example, when the resin containing a polar functional group is an ethylene-ethyl acrylate copolymer (EEA), the kneading may be performed at a temperature of preferably 160° C. or higher, more preferably 175° C. or higher, and even more preferably 190° C. or higher. In addition, the kneading may be performed at a temperature of preferably 270° C. or lower, more preferably 260° C. or lower, and even more preferably 250° C. or lower.

[0092] In the above step, for example, when the resin containing a polar functional group is an ethylene-methacrylic acid copolymer (EMAA), the kneading may be performed at a temperature of preferably 160° C. or higher, more preferably 175° C. or higher, and even more preferably 190° C. or higher. In addition, the kneading may be performed at a temperature of preferably 270° C. or lower, more preferably 260° C. or lower, and even more preferably 250° C. or lower.

[0093] In the above step, for example, when the resin containing a polar functional group is an ethylene-acrylic acid copolymer (EAA), the kneading may be performed at a temperature of preferably 160° C. or higher, more preferably 175° C. or higher, and even more preferably 190° C. or higher. In addition, the kneading may be performed at a temperature of preferably 270° C. or lower, more preferably 260° C. or lower, and even more preferably 250° C. or lower.

[0094] In the above process, for example, when the resin containing a polar functional group is an ethylene-acrylic acid-maleic anhydride ternary copolymer, the kneading can be performed at preferably 160°C or higher, more preferably 175°C or higher, and even more preferably 190°C or higher. In addition, the kneading can be performed at preferably 270°C or lower, more preferably 260°C or lower, and even more preferably 250°C or lower. In the above process, for example, when the resin containing a polar functional group is an ethylene-vinyl acetate-maleic anhydride ternary copolymer, the extrusion can be performed at preferably 160°C or higher, more preferably 175°C or higher, and even more preferably 190°C or higher. In addition, the extrusion can be performed at preferably 250°C or lower, more preferably 240°C or lower, and even more preferably 230°C or lower.

[0095] Mixing of raw materials such as polypropylene resin and resin containing polar functional groups may be performed by a mixer such as a high-temperature agitator, a Henschel mixer, a tumbler type mixer, a Banbury mixer, or a kneader mixer. Melt plasticization and kneading of the mixed raw materials may be performed by, for example, a single-screw kneading extruder or a twin-screw kneading extruder. As these kneading extruders, devices known in the art may be used. Preferably, the process includes at least heating and kneading treatment by a twin-screw kneading extruder. As the twin-screw kneading extruder, a co-rotating twin-screw kneading extruder may be used, or a counter-rotating twin-screw kneading extruder may be used. By performing the kneading treatment by the twin-screw kneading extruder, a resin composition that is a kneaded product in which the raw materials are more uniformly dispersed can be obtained.

[0096] The resin composition obtained in the above step as a kneaded product may be directly subjected to a sheet molding step without being pelletized, thereby making it possible to omit the pelletizing step. The resin composition that is the kneaded product obtained in the above step may be pelletized. The pelletized resin composition that is the kneaded product may be subjected to a sheet molding step.

[0097] [Sheet forming process]

[0098] In the sheet molding step, the resin composition obtained in the resin composition preparation step is molded to obtain a single-layer sheet. For example, the resin composition obtained in the resin composition preparation step is transferred to a sheet molding machine, and the resin composition is molded using the sheet molding machine to form a sheet. The temperature during molding of the sheet may be set preferably to a melting temperature of the resin composition or higher, for example, 160°C to 270°C. The molding pressure may also be set appropriately.

[0099] When forming the sheet, various molding machines such as a T-die extruder and a calendar molding machine can be used. After the sheet is formed by the molding machine, the temperature of the take-up roll may be appropriately set immediately after the sheet is formed to a predetermined thickness, and the sheet may be cooled and taken up as a raw roll and wound up. The thickness of the sheet may be, for example, 100 μm or more.

[0100] In the molding, for example, the resin composition may be extruded from a molding machine as it is without being pelletized, or the pelletized resin composition may be melted and the molten resin composition may be extruded from a molding machine. The extrusion temperature may be appropriately selected by a person skilled in the art depending on the type and content of the resin containing a polar functional group contained in the resin composition. In the above process, for example, when the resin containing a polar functional group is an ethylene-methyl acrylate copolymer (EMA), the extrusion may be carried out at a temperature of preferably 160° C. or higher, more preferably 175° C. or higher, and even more preferably 190° C. or higher. The extrusion may be carried out at a temperature of preferably 270° C. or lower, more preferably 260° C. or lower, and even more preferably 250° C. or lower.

[0101] In the above process, for example, when the resin containing a polar functional group is an ethylene-vinyl acetate copolymer (EVA), the extrusion may be carried out at a temperature of preferably 160° C. or higher, more preferably 175° C. or higher, and even more preferably 190° C. or higher. The extrusion may be carried out at a temperature of preferably 250° C. or lower, more preferably 240° C. or lower, and even more preferably 230° C. or lower.

[0102] In the above step, for example, when the resin containing a polar functional group is an ionomer, the extrusion may be performed at a temperature of preferably 160° C. or higher, more preferably 175° C. or higher, and even more preferably 190° C. or higher. Also, the extrusion may be performed at a temperature of preferably 270° C. or lower, more preferably 260° C. or lower, and even more preferably 250° C. or lower.

[0103] In the above process, for example, when the resin containing a polar functional group is an ethylene-methyl methacrylate copolymer (EMMA), the extrusion may be carried out at a temperature of preferably 160° C. or higher, more preferably 175° C. or higher, and even more preferably 190° C. or higher. The extrusion may be carried out at a temperature of preferably 270° C. or lower, more preferably 260° C. or lower, and even more preferably 250° C. or lower.

[0104] In the above process, for example, when the resin containing a polar functional group is an ethylene-ethyl acrylate copolymer (EEA), the extrusion may be carried out at a temperature of preferably 160° C. or higher, more preferably 175° C. or higher, and even more preferably 190° C. or higher. The extrusion may be carried out at a temperature of preferably 270° C. or lower, more preferably 260° C. or lower, and even more preferably 250° C. or lower.

[0105] In the above process, for example, when the resin containing a polar functional group is an ethylene-methacrylic acid copolymer (EMAA), the extrusion may be carried out at a temperature of preferably 160° C. or higher, more preferably 175° C. or higher, and even more preferably 190° C. or higher. The extrusion may be carried out at a temperature of preferably 270° C. or lower, more preferably 260° C. or lower, and even more preferably 250° C. or lower.

[0106] In the above process, for example, when the resin containing a polar functional group is an ethylene-acrylic acid copolymer (EAA), the extrusion may be carried out at a temperature of preferably 160° C. or higher, more preferably 175° C. or higher, and even more preferably 190° C. or higher. Also, the extrusion may be carried out at a temperature of preferably 270° C. or lower, more preferably 260° C. or lower, and even more preferably 250° C. or lower.

[0107] In the above process, for example, when the resin containing a polar functional group is an ethylene-acrylic acid-maleic anhydride ternary copolymer, the extrusion may be performed at preferably 160°C or higher, more preferably 175°C or higher, and even more preferably 190°C or higher. In addition, the extrusion may be performed at preferably 270°C or lower, more preferably 260°C or lower, and even more preferably 250°C or lower. In the above process, for example, when the resin containing a polar functional group is an ethylene-vinyl acetate-maleic anhydride ternary copolymer, the extrusion may be performed at preferably 160°C or higher, more preferably 175°C or higher, and even more preferably 190°C or higher. In addition, the extrusion may be performed at preferably 250°C or lower, more preferably 240°C or lower, and even more preferably 230°C or lower.

[0108] [Container body forming process]

[0109] In the container body forming process, the sheet obtained in the sheet forming process is softened by heating, and the softened sheet is brought into close contact with a forming die by suction to form a recess in which the packaged item is accommodated, thereby forming the container body. Vacuum forming or vacuum pressure forming is used as the forming method. Plug assist is also performed depending on the drawing ratio. The depth of the recess can be appropriately set according to the application, and for example, the depth of the recess may be preferably 1 to 5 cm. In addition, deep drawing molding with a large drawing ratio, which is the value obtained by dividing the depth of the container by the inner dimension of the opening of the container, may be performed. The sheet surface temperature immediately before forming in the forming machine measured with a non-contact radiation thermometer is preferably heated to 140°C to 170°C, the heating time is preferably set to 6 to 15 seconds, and the forming time is preferably set to 6 to 15 seconds.

[0110] In addition, when manufacturing deep-draw containers such as ice cream containers and drink cups, the container body may be molded using the solid-phase molding machine described in JP 2023-012756 A. In this specification, the solid-phase molding machine means a machine that manufactures a molded product by a solid-phase molding method in which a laminate is heated and a laminate in a non-molten (solid or semi-solid) state is molded. Specifically, the non-molten laminate is a laminate that is heated at a temperature lower than the melting point of the resin with the highest melting point contained in the laminate and at a temperature higher than the crystallization temperature of the resin with the lowest crystallization temperature contained in the laminate.

[0111] In the solid-phase molding method, the temperature of the laminate during molding is lower than in the melt molding method in which a laminate in a molten state is molded, and the amount of heat required for heating the laminate is smaller. In addition, since the amount of heat required for heating an inorganic filler is generally the same as that required for heating the resin, the amount of heat required for heating a laminate containing an inorganic filler in the solid-phase molding method is smaller than that required for a laminate not containing an inorganic filler. Therefore, the use of the solid-phase molding method enables energy saving by reducing the amount of electricity required in the manufacturing process.

[0112] In the method for manufacturing a container according to the present embodiment, the solid-phase molding method is preferably a solid-phase pressure-air molding method. That is, in the solid-phase pressure-air molding method, the container body is molded using a solid-phase pressure-air molding machine. In this specification, the solid-phase pressure-air molding machine means a machine for manufacturing a molded product by a solid-phase pressure-air molding method in which a laminate is heated, a laminate in a non-molten (solid or semi-solid) state is pressurized with compressed air, and the laminate is closely attached to a mold to be molded. The heating temperature of the laminate to obtain a non-molten laminate in the solid-phase pressure-air molding method is the same as that of the solid-phase molding method described above. The solid-phase pressure-air molding method enables energy saving in the manufacturing process, as with the above-mentioned solid-phase molding method. Since the solid-phase pressure-air molding machine can apply high pressure to the laminate, it is suitable for manufacturing a deep-drawn container that requires the laminate to be deeply stretched. That is, the method for manufacturing a container according to the present embodiment can preferably be a method for manufacturing a deep-drawn container that includes molding the laminate with a solid-phase pressure-air molding machine.

[0113] The container body molding process is not limited to the thermoforming method, and may be an injection molding method in which a compound of the specific polypropylene resin and a resin containing a polar functional group is melted and plasticized by heating and kneading, and then the compound is injected into a mold, filled, pressure-held, and cooled to produce a container.

[0114] [Heat sealing process]

[0115] The container body obtained in the container molding step is heat-sealed to a previously prepared lid material to obtain a container in which the contents, such as ice cream, are sealed. In the heat sealing step, the contents, such as ice cream, are first filled into the container body formed in the container body molding step. Next, the flange surface of the container body and the surface of the lid material on which the hot melt composition is applied are heated while being pressed against each other. The heating temperature is preferably 170°C or less, more preferably 160°C or less. The pressing pressure is preferably 2 kgf / cm. 2 The pressure bonding time is 1.0 second or more.

[0116] 2. Second embodiment (example of single layer sheet)

[0117] (1) Seat configuration

[0118] The configuration of the sheet according to this embodiment will be described below: The sheet according to this embodiment is a single-layer sheet. The sheet according to this embodiment is formed from a first resin composition containing a polypropylene resin and a resin containing a polar functional group. All of the explanations regarding the resin composition described in 1. "(1) Configuration of the container" above also apply to the first resin composition in the second embodiment. Therefore, the explanation of the first resin composition is omitted.

[0119] (2) Seat manufacturing method

[0120] The sheet manufacturing method according to this embodiment includes a first resin composition preparation step of mixing a polypropylene resin and a resin containing a polar functional group to prepare a first resin composition, and a sheet molding step of extruding the first resin composition to form a sheet. Note that, for the first resin composition preparation step and the sheet molding step, all of the explanations regarding the resin composition preparation step and the sheet molding step described in "(2) Container manufacturing method" in 1 above also apply to the second embodiment. Therefore, the explanations regarding the first resin composition preparation step and the sheet molding step according to the second embodiment will be omitted.

[0121] (3) Physical properties of the sheet

[0122] [Peel strength]

[0123] In the single-layer sheet of this embodiment, when a hot melt tape coated with a hot melt composition is laminated to the sheet and the hot melt tape is peeled from the sheet at 25°C, the peel strength is preferably 0.5 kgf / 15 mm or more, preferably 0.7 kgf / 15 mm or more, more preferably 0.9 kgf / 15 mm or more, and even more preferably 1.1 kgf / 15 mm or more.

[0124] In the sheet of this embodiment, when a hot melt tape coated with a hot melt composition is adhered to the sheet and the hot melt tape is peeled from the sheet at 0°C, the peel strength is preferably 0.5 kgf / 15 mm or more, preferably 0.7 kgf / 15 mm or more, more preferably 0.9 kgf / 15 mm or more, and even more preferably 1.1 kgf / 15 mm or more.

[0125] (Measurement of peel strength after storage at room temperature)

[0126] <Lid material>

[0127] A hot melt composition (product name "TOYOMELT H-301H (EVA type, softening point: 70°C)" manufactured by Toyochem Co., Ltd.) was applied at a rate of 20 g / m on the polyethylene side of the substrate, which was laminated in the order of polyethylene (PE) / polyethylene terephthalate sheet (PET) / paper / polyethylene terephthalate sheet (PET). 2 After drying, the lid material is obtained.

[0128] <Sheet>

[0129] The components are kneaded in a single-screw extruder (screw diameter: φ25 mm, L / D=30) to prepare a resin composition. The resin composition is extruded using a T-die extrusion molding machine (T-die width: 350 mm (coat hanger die), lip opening: 0.8 mm) set at a molding temperature of 230°C, an extrusion screw rotation speed of 180 rpm, a cooling roll temperature of 90°C, and a take-up speed of 0.9 m / min to obtain a single-layer sheet with a thickness of 700 μm.

[0130] <Sample Preparation>

[0131] Cut the lid material and the monolayer sheet to a width of 15 mm and a length of 100 mm, place the monolayer sheet on the surface of the cut lid material on which the hot melt composition was applied, and heat seal under the following heat sealing conditions using a semi-automatic sealing machine SN-1 manufactured by Shinwa Machinery Co., Ltd. to prepare a peel strength test sample. The sample is stored at room temperature.

[0132] <Heat sealing conditions>

[0133] Press pressure: 2kgf / cm 2 Press time: 1 second Heat seal temperature: 120℃

[0134] Thereafter, a peel test is carried out under the following peel conditions using a universal testing machine (product name "Strograph VES5D", manufactured by Toyo Seiki Seisakusho, Ltd.) to measure the peel strength.

[0135] <Peeling conditions>

[0136] Peel angle: 90° (has a mechanism to maintain a peel angle of 90° at all times during the peel test.) Peeling speed: 150mm / min

[0137] The peel strength is measured as the average value (unit: kgf / 15 mm) of the points where the peeling stabilizes (excluding the beginning and end). The measurement is carried out twice. The peel strength is evaluated as follows:

[0138] Peel strength especially good (A): 0.8kgf / 15mm or more: Good peel strength (B): 0.5kgf / 15mm or more, less than 0.8kgf / 15mm Insufficient peel strength (C): 0.3kgf / 15mm or more and less than 0.5kgf / 15mm Unbonded (D): Less than 0.3kgf / 15mm

[0139] (Peeling behavior after storage at room temperature)

[0140] In the measurement of peel strength, the surface where the lid material was peeled from the monolayer sheet was visually observed for cohesive failure (there is a break line in the sealant layer) in the sealant layer of the lid material (hot melt composition side) and interfacial peeling (there is a break line at the interface) in the seal layer between the lid material and the monolayer sheet. The peeling state between the lid material and the monolayer sheet will be explained below using figures. FIG. 3 is a cross-sectional view showing the bonding state between the lid material and the monolayer sheet before the lid material is peeled from the monolayer sheet. As shown in FIG. 3, the lid material is composed of a base material layer 31 and a sealant layer 32 formed from a hot melt composition. The monolayer sheet is composed of a seal layer 33 formed from a resin composition containing a polypropylene resin and a resin containing a polar functional group. The lid material and the monolayer sheet are in contact with each other at the sealant layer 32 and the seal layer 33, forming an interface.

[0141] Fig. 4 is a diagram showing how peeling due to cohesive failure occurs in the sealant layer (hot melt composition) of the lid material when the lid material is peeled off from the monolayer sheet. As shown in Fig. 4, cohesive failure occurs in a deep portion (far from the monolayer sheet side) of the sealant layer 32 of the lid material, a fracture line exists in a deep portion of the sealant layer 32, and peeling occurs in a deep portion, so the peel strength is stable and high. Cohesive failure can be confirmed by checking whether the hot melt composition is transferred to the seal layer side surface of the monolayer sheet after peeling.

[0142] Fig. 5 is a diagram showing how peeling due to cohesive failure occurs in the sealant layer (hot melt composition) of the lid material when the lid material is peeled off from the monolayer sheet. As shown in Fig. 5, cohesive failure occurs in a shallow portion (close to the monolayer sheet side) of the sealant layer 32 of the lid material, a fracture line exists in a shallow portion of the sealant layer 32, and peeling occurs in a shallow portion, so the peel strength is stable but low.

[0143] Figure 6 is a diagram showing how peeling due to cohesive failure occurs near the interface between the sealant layer of the cover material and the seal layer of the single-layer sheet when the cover material is peeled off from the single-layer sheet. As shown in Figure 6, cohesive failure occurs in the sealant layer, peeling occurs at the interface between the sealant layer and the sealant layer, and there are areas where there is a fracture line in the sealant layer and areas where there is a fracture line at the interface between the sealant layer and the sealant layer, so the peel strength is uneven. As a result, stick-slip occurs during peeling. The peeling morphology is evaluated as follows.

[0144] A (Good) Usable: No stick-slip phenomenon as shown in Figure 10. B (Fair) Usable: There is a slight stick-slip phenomenon as shown in Figure 11. C (Fail): Stick-slip phenomenon occurs as shown in Figure 12.

[0145] (Measurement of peel strength after freezing storage)

[0146] The cover material and the single layer sheet are manufactured under the same conditions as those used in the measurement of the peel strength after storage at room temperature.

[0147] <Sample Preparation>

[0148] The lid material and the monolayer sheet are each cut to a width of 15 mm and a length of 100 mm, the monolayer sheet is placed on the surface of the cut lid material on which the hot melt composition has been applied, and heat sealed under the following heat sealing conditions using a semi-automatic sealing machine SN-1 manufactured by Shinwa Kikai Co., Ltd. to prepare a peel strength test sample. The sample is placed in a thermostatic chamber ("PU-3J", manufactured by ESPEC Co., Ltd.) and frozen and stored at -18°C for at least 24 hours.

[0149] <Heat sealing conditions>

[0150] Press pressure: 2kgf / cm 2 Press time: 1 second Heat seal temperature: 160℃

[0151] Thereafter, a peel test is carried out under the same peel conditions as in the peel test after storage at room temperature, and the peel strength is measured.

[0152] The sample was removed from the thermostatic chamber and the surface temperature of the sample was measured with a compact thermography camera (Teledyne FLIR LLC). The peel test was started when the surface temperature reached 0°C. The peel strength is measured as the average value (unit: kgf / 15 mm) of the points where the peeling stabilizes (excluding the beginning and end). Measurements are performed twice. The evaluation criteria for peel strength are the same as those for peel strength after storage at room temperature.

[0153] (Peeled form after frozen storage)

[0154] In the measurement of peel strength, the surface of the lid material peeled from the monolayer sheet was visually observed for cohesive failure in the sealant layer (hot melt composition side) of the lid material and interfacial peeling between the seal layer of the lid material and the monolayer sheet. The evaluation criteria for the peeling state are the same as those for the peeling state after storage at room temperature.

[0155] [Haze value]

[0156] The sheet of this embodiment has a haze value at a thickness of 1.0 mm, as measured according to JIS K7136, of preferably 70% or less, more preferably 65% ​​or less, even more preferably 60% or less, and even more preferably 50% or less.

[0157] (Haze value measurement)

[0158] Using a haze meter "HZ-V3" (manufactured by Suga Test Instruments Co., Ltd.), the sheet is measured in accordance with JIS K7136. The haze value % and thickness are measured at four or more points on the sheet and plotted. The haze value for a specific thickness is calculated from the approximate straight line of the plot.

[0159] [Transparency]

[0160] When the sheet is visually inspected, the sheet is checked for transparency. Transparency is evaluated according to the following criteria.

[0161] A: The opposite side of the sheet can be seen visually. B: The opposite side of the sheet is cloudy and difficult to see. C: Unable to see the other side of the sheet

[0162] [Odor]

[0163] The odor is checked immediately after the sheet is formed. The odor is evaluated according to the following criteria.

[0164] A: No odor B: Slight odor C: Odor

[0165] 3. Third embodiment (example of multilayer sheet)

[0166] (1) Structure of the multi-layer sheet

[0167] <Two-layer sheet>

[0168] As shown in FIG. 7, the multilayer sheet of this embodiment is a two-layer sheet having, for example, a base layer 71 and a seal layer 72.

[0169] [Base material layer]

[0170] The base layer 71 may be made of a second resin composition containing a polypropylene (PP) resin from the viewpoint of adhesion to the seal layer 72. The polypropylene (PP) resin is the same as that described in the first embodiment, and therefore the description will be omitted. From the viewpoint of improving rigidity, the second resin composition may contain an inorganic filler. Examples of such inorganic fillers include talc, calcium carbonate, magnesium carbonate, calcium oxide, magnesium oxide, calcium hydroxide, magnesium hydroxide, aluminum hydroxide, calcium silicate, magnesium silicate, calcium sulfate, barium sulfate, calcium sulfite, titanium dioxide, silicon dioxide, glass, clay, and diatomaceous earth. The inorganic filler may be, for example, one or a combination of two or more of these inorganic fillers, and is preferably talc and / or calcium carbonate, and more preferably talc.

[0171] The resin constituting the base layer 71 preferably has a transparency to such an extent that the contents can be visually confirmed when the container body is formed, and also has cold impact resistance so that it will not break even under freezing conditions. Examples of commercially available products of such polyolefin resins include cold-resistant transparent block polypropylene resins (Qualia (registered trademark), manufactured by SunAllomer Co., Ltd.).

[0172] [Sealing layer]

[0173] 7, the sealing layer 72 is provided in contact with one main surface of the base layer 71. The sealing layer 72 is formed from a first resin composition including a polypropylene resin and a resin including a polar functional group.

[0174] The polypropylene resin and the resin containing a polar functional group forming the sealing layer 72 are all applicable to the polypropylene resin and the resin containing a polar functional group in the first embodiment, so the description thereof will be omitted.

[0175] <Multi-layer sheet with a laminated structure of three or more layers>

[0176] As shown in FIG. 8, the multilayer sheet of this embodiment is a three-layer sheet having a base layer 81, an intermediate layer 82, and a seal layer 83, for example.

[0177] [Base material layer]

[0178] In the case of a three-layer sheet, the second resin composition containing the polypropylene (PP) resin used in the base layer of the single-layer sheet according to the second embodiment may be used as the resin forming the base layer 81, and further, polyethylene resin, polyester resin, polystyrene resin, etc., which have low adhesiveness to the seal layer 83 may also be used. The polyethylene resin may be, for example, low-density polyethylene resin (LDPE: Low Density Polyethylene), high-density polyethylene resin (HDPE: High Density Polyethylene), very low-density polyethylene resin (VLDPE: Very Low Density Polyethylene), linear low-density polyethylene resin (LLDPE: Linear Low Density Polyethylene), ethylene copolymers such as ethylene-vinyl acetate copolymer (EVA resin), ultra-high molecular weight polyethylene resin (UHMW-PE: Ultra High Molecular Weight-Polyethylene), or a combination thereof.

[0179] The polyester resin is a polymer in which monomers are polymerized through ester bonds. The polyester resin may be, for example, polyethylene terephthalate resin (PET), polyethylene naphthalate resin (PEN), polybutylene terephthalate resin (PBT), polylactic acid resin (PLA), polycarbonate resin (PC), polybutylene adipate terephthalate resin (PBAT), polybutylene succinate resin (PBS), polyhydroxyalkanoate resin (PHA), or a combination of two or more of these.

[0180] [Middle layer]

[0181] The same description as for the sealing layer 72 in the two-layer sheet applies to the sealing layer 83, so a description thereof will be omitted.

[0182] The intermediate layer 82 is formed from a resin having good adhesion to the seal layer 83. The intermediate layer 82 is sandwiched between the base material layer 81 and the seal layer 83, and can function as an adhesive layer that bonds the base material layer 81 and the seal layer 83. For this reason, the resin forming the intermediate layer 82 has good adhesion to both the base material layer 81 and the seal layer 83. The intermediate layer 82 may be formed from a first resin composition containing a polyolefin resin that forms the seal layer 83. In addition, there is no limitation on the resin forming the intermediate layer 82 as long as it contains a polypropylene resin that has good adhesion to the seal layer 83. The first resin composition forming the intermediate layer 82 is the same as the first resin composition forming the seal layer 72, so the description will be omitted.

[0183] (2) Manufacturing method of multilayer sheet

[0184] The method for producing the multilayer sheet of the present embodiment can include, for example, a resin composition preparation step and a multilayer extrusion molding step.

[0185] [Resin composition preparation process]

[0186] Here, a case where a three-layer sheet is manufactured will be described. When a two-layer sheet is manufactured, a resin composition for forming an intermediate layer is not prepared. In the resin composition preparation step, a first resin composition for forming a seal layer, a second resin composition for forming a base layer, and a third resin composition for forming an intermediate layer are prepared. For the second resin composition for forming the base layer and the third resin composition for forming the intermediate layer, the explanation of the resin composition preparation step in the first embodiment applies except that the second resin composition for forming the base layer and the third resin composition for forming the intermediate layer are used instead of the first resin composition containing a polypropylene resin and a resin containing a polar functional group, and therefore the explanation will be omitted.

[0187] [Multi-layer extrusion molding process]

[0188] In the multilayer extrusion process, a first resin composition forming a seal layer, a second resin composition forming a base layer, and a third resin composition forming an intermediate layer are extruded, and the resin layers are laminated to each other to obtain a multilayer sheet. The multilayer sheet can be obtained, for example, by using a multilayer co-extrusion molding machine 300 shown in FIG. 9. The multilayer co-extrusion molding machine 300 may have an extruder 301 for a base layer, an extruder 302 for an intermediate layer, an extruder 303 for a seal layer, a feed block 304, and a die 305. The multilayer co-extrusion molding machine 300 co-extrudes a three-layer structure multilayer sheet 306 in which the base layer, the intermediate layer, and the seal layer are laminated, with the intermediate layer containing the third resin composition forming the intermediate layer as the middle layer and the base layer and the seal layer as the surface layers. The intermediate layer extruder 302 extrudes the resin composition forming the intermediate layer prepared in the resin composition preparation step, and the base layer extruder 301 may extrude a different type of resin composition from the resin composition extruded from the intermediate layer extruder 302, or may extrude the same resin composition. When a two-layer sheet is produced, for example, the intermediate layer extruder 302 may not be used, or the resin composition forming the base layer may be extruded from the intermediate layer extruder 302. Furthermore, when a laminated sheet of three or more layers is produced, a multilayer co-extrusion molding machine equipped with a plurality of intermediate layer extruders may be used.

[0189] The single-layer sheet or multi-layer sheet produced as described above may be used to form a container body via the container body forming step described in 1. "(2) Container manufacturing method" above.

[0190] (3) Physical properties of multilayer sheets

[0191] The physical properties of the multilayer sheet of this embodiment are all the same as those described in 2. "(3) Physical properties of the sheet" above, and therefore a description thereof will be omitted.

[0192] The present technology can also adopt the following configuration. [1] Polypropylene resin, A container body formed from a resin composition including a resin having a polar functional group; A lid material joined to the container body so as to seal the opening of the container body; A container having [2] The container according to [1], wherein the polar functional group is an oxygen-containing group. [3] The container according to [1] or [2], wherein the content of the polypropylene resin is 30 to 99 mass % based on the mass of the resin composition. [4] The container according to any one of [1] to [3], wherein the content of the resin containing a polar functional group is 1 to 70 mass % based on the mass of the resin composition. [5] The container according to any one of [1] to [4], wherein the lid material has a sealant layer on the side to be bonded to the resin composition. [6] The container according to [5], wherein the sealant layer has a hot melt composition. [7] The container according to [6], wherein the hot melt composition comprises an ethylene-vinyl acetate copolymer resin. [8] The container according to [6] or [7], wherein when the container body and the lid material to which a hot melt composition has been applied are bonded together and the lid material is peeled off from the container body at 25°C, cohesive failure occurs in the hot melt composition. [9] The container according to [6] or [7], wherein the container body and the lid material to which a hot melt composition has been applied are bonded together, and when the lid material is peeled off from the container body at 0°C, cohesive failure occurs in the hot melt composition.

[10] Polypropylene resin, A sheet formed from a resin composition comprising: a resin having a polar functional group.

[11] A base layer; A seal layer disposed on one surface side of the base layer; A sheet having The sealing layer is made of a polypropylene resin, and a resin including a polar functional group; The sheet, wherein the base layer is formed from a second resin composition that is the same as or different from the first resin composition.

[12] The sheet according to

[10] or

[11] , wherein when a hot melt tape having a hot melt composition applied thereto is adhered to the sheet and the hot melt tape is peeled from the sheet at 25°C, the peel strength is 0.5 kgf / 15 mm or more.

[13] The sheet according to

[10] or

[11] , wherein a hot melt tape having a hot melt composition applied thereto is laminated to the sheet, and the hot melt tape has a peel strength of 0.5 kgf / 15 mm or more when peeled from the sheet at 0°C.

[0193] 4. Working Example

[0194] The present invention will be described in more detail below based on examples. Note that the examples described below are representative examples of the present invention, and the scope of the present invention is not limited to these examples. The evaluation methods used in the examples are the same as those described in 2.(3) Physical properties of the sheet above.

[0195] Example 1

[0196] Polypropylene resin A (product name: Novatec (registered trademark) FY6, manufactured by Japan Polypropylene Corporation) was supplied to extruder 301 for base layer of multilayer co-extrusion molding machine 300 (manufactured by LAB TECH Engineering Co., Ltd.) via a hopper so that the amount was 100 mass% relative to the mass of the second resin composition, and polypropylene resin B (product name: Novatec (registered trademark) EG6D, manufactured by Japan Polypropylene Corporation) was supplied to extruder 303 for sealing layer via a hopper so that the amount was 70 mass% relative to the mass of the first resin composition, and ethylene-methyl acrylate copolymer (Rexpearl (registered trademark) EB050S, manufactured by Japan Polyethylene Corporation) was supplied to extruder 303 for sealing layer via a hopper so that the amount was 30 mass% relative to the mass of the first resin composition, and the resin compositions supplied to extruder 301 for base layer and extruder 303 for sealing layer were co-extruded to obtain a multilayer sheet having a two-layer structure.

[0197] The cylinder temperature and adapter temperature of the base layer extruder 301 (model number: LE25-30 / C (manufactured by LAB TECH Engineering), L / D=30, φ25 mm) and the sealing layer extruder 303 (model number: LE25-30 / C (manufactured by LAB TECH Engineering), L / D=30, φ25 mm) were each set to 200° C. The screw speed of each of the base layer extruder 301 and the sealing layer extruder 303 was set to 20 rpm.

[0198] A multilayer sheet having a seal layer thickness of 50 μm and a base layer thickness of 650 μm (hereinafter, also referred to as "multilayer sheet of Example 1") was obtained by the multilayer extrusion molding. The peel strength of the obtained multilayer sheet was measured after storage at room temperature and after freezing storage according to the method described in the second embodiment. The multilayer sheet sealed with a lid material at 120°C after storage at room temperature had a peel strength of 1.22 kgf / 15 mm, and the peel morphology was evaluated as A (good), in which cohesive failure occurred on the sealant layer side of the lid material as shown in FIG. 4, and the position of cohesive failure in the depth direction was substantially constant. The multilayer sheet sealed with a lid material at 160°C after freezing storage had a peel strength of 1.63 kgf / 15 mm, and the peel morphology was evaluated as A (good), in which cohesive failure occurred on the sealant layer side of the lid material as shown in FIG. 4, and the position of cohesive failure in the depth direction was substantially constant. The measurement results are shown in Table 1 below.

[0199] [Table 1]

[0200] Example 2

[0201] A multilayer sheet having a sealing layer thickness of 50 μm and a base layer thickness of 650 μm (hereinafter also referred to as the "multilayer sheet of Example 2") was obtained in the same manner as in Example 1, except that polypropylene resin B (product name: Novatec (registered trademark) EG6D, manufactured by Japan Polypropylene Corporation) was supplied via a hopper to the sealing layer extruder 303 so that the amount was 85 mass% of the first resin composition, and ethylene-methyl acrylate copolymer (Rexpearl (registered trademark) EB050S, manufactured by Japan Polyethylene Corporation) was supplied to the sealing layer extruder 303 so that the amount was 15 mass% of the first resin composition.

[0202] The peel strength of the multilayer sheet of Example 2 obtained was measured by the same method as in Example 1. The multilayer sheet sealed with a lid at 120°C and stored at room temperature had a peel strength of 1.20 kgf / 15 mm, and the peel morphology was evaluated as B (acceptable), in which cohesive failure occurred on the sealant layer side of the lid as shown in Figure 5, and the depth position of the cohesive failure varied within the sealant layer. The multilayer sheet sealed with a lid at 160°C and stored in a freezer had a peel strength of 1.70 kgf / 15 mm, and the peel morphology was evaluated as B (acceptable), in which cohesive failure occurred on the sealant layer side of the lid as shown in Figure 5, and the depth position of the cohesive failure varied within the sealant layer. The measurement results are shown in Table 1 above.

[0203] Example 3

[0204] A multilayer sheet having a sealing layer thickness of 50 μm and a base layer thickness of 650 μm (hereinafter also referred to as the "multilayer sheet of Example 3") was obtained in the same manner as in Example 1, except that polypropylene resin B (product name: Novatec (registered trademark) EG6D, manufactured by Japan Polypropylene Corporation) was supplied via a hopper to the sealing layer extruder 303 so as to account for 40 mass% of the mass of the first resin composition, and ethylene-vinyl acetate copolymer (Ultrathene (registered trademark) UE630, manufactured by Tosoh Corporation) was supplied to account for 60 mass% of the mass of the first resin composition.

[0205] The peel strength of the multilayer sheet of Example 3 obtained was measured by the same method as in Example 1. The multilayer sheet sealed with a lid at 120°C and stored at room temperature had a peel strength of 1.20 kgf / 15 mm, and the peel morphology was evaluated as A (good), in which cohesive failure occurred on the sealant layer side of the lid as shown in Figure 4, and the position of cohesive failure in the depth direction was substantially constant. The multilayer sheet sealed with a lid at 160°C and stored in a freezer had a peel strength of 1.39 kgf / 15 mm, and the peel morphology was evaluated as A (good), in which cohesive failure occurred on the sealant layer side of the lid as shown in Figure 4, and the position of cohesive failure in the depth direction was substantially constant. The measurement results are shown in Table 1 above.

[0206] Example 4

[0207] A multilayer sheet having a sealing layer thickness of 50 μm and a base layer thickness of 650 μm (hereinafter also referred to as the "multilayer sheet of Example 4") was obtained in the same manner as in Example 1, except that polypropylene resin B (product name: Novatec (registered trademark) EG6D, manufactured by Japan Polypropylene Corporation) was supplied via a hopper to the sealing layer extruder 303 so that the amount of polypropylene resin B was 75 mass% relative to the mass of the first resin composition, ionomer (Himilan (registered trademark) 1706, manufactured by Dow Mitsui Polychemicals) was 20 mass% relative to the mass of the first resin composition, and maleic anhydride grafted polyolefin resin (Fusabond (registered trademark) N493, manufactured by DuPont) was 5 mass% relative to the mass of the first resin composition.

[0208] The peel strength of the multilayer sheet of Example 4 obtained was measured by the same method as in Example 1. The multilayer sheet sealed with a lid at 120°C and stored at room temperature had a peel strength of 1.16 kgf / 15 mm, and the peel morphology was evaluated as A (good), in which cohesive failure occurred on the sealant layer side of the lid as shown in Figure 4, and the position of cohesive failure in the depth direction was substantially constant. The multilayer sheet sealed with a lid at 160°C and stored in a freezer had a peel strength of 1.25 kgf / 15 mm, and the peel morphology was evaluated as A (good), in which cohesive failure occurred on the sealant layer side of the lid as shown in Figure 4, and the position of cohesive failure in the depth direction was substantially constant. The measurement results are shown in Table 1 above.

[0209] Example 5

[0210] A multilayer sheet having a sealing layer thickness of 50 μm and a base layer thickness of 650 μm (hereinafter also referred to as the "multilayer sheet of Example 5") was obtained in the same manner as in Example 1, except that polypropylene resin A (product name: Novatec (registered trademark) FY6, manufactured by Japan Polypropylene Corporation) was supplied via a hopper to the sealing layer extruder 303 so that 80 mass% of the mass of the first resin composition and maleic anhydride grafted ethylene-vinyl acetate copolymer (EVA) (Fusabond (registered trademark) C190, manufactured by DuPont) was supplied to the sealing layer extruder 303 so that 80 mass% of the mass of the first resin composition and 20 mass% of the mass of the first resin composition were supplied to the sealing layer extruder 303 via a hopper.

[0211] The peel strength of the multilayer sheet of Example 5 obtained was measured by the same method as in Example 1. The multilayer sheet sealed with a lid at 120°C and stored at room temperature had a peel strength of 1.03 kgf / 15 mm, and the peel morphology was evaluated as B (acceptable), in which cohesive failure occurred on the sealant layer side of the lid as shown in Figure 5, and the depth position of the cohesive failure varied within the sealant layer. The multilayer sheet sealed with a lid at 160°C and stored in a freezer had a peel strength of 1.02 kgf / 15 mm, and the peel morphology was evaluated as B (acceptable), in which cohesive failure occurred on the sealant layer side of the lid as shown in Figure 5, and the depth position of the cohesive failure varied within the sealant layer. The measurement results are shown in Table 1 above.

[0212] Comparative Example 1

[0213] A multilayer sheet having a sealing layer thickness of 50 μm and a base layer thickness of 650 μm (hereinafter also referred to as "multilayer sheet of Comparative Example 1") was obtained in the same manner as in Example 1, except that polypropylene resin B (product name: Novatec (registered trademark) EG6D, manufactured by Japan Polypropylene Corporation) was supplied to the sealing layer extruder 303 via a hopper so that it was 100 mass% relative to the mass of the first resin composition.

[0214] The peel strength of the multilayer sheet of Comparative Example 1 obtained was measured by the same method as in Example 1. The multilayer sheet sealed with a lid at 120°C and stored at room temperature had a peel strength of 1.21 kgf / 15 mm, and the peel morphology was a mixture of cohesive failure on the sealant layer side of the lid and interfacial peeling as shown in Figure 6, which was rated C (unacceptable). Stick-slip occurred continuously, so it was unusable. The multilayer sheet sealed with a lid at 160°C and stored in a freezer had a peel strength of 1.71 kgf / 15 mm, and the peel morphology was a mixture of cohesive failure on the sealant layer side of the lid and interfacial peeling as shown in Figure 6, which was rated C (unacceptable). Stick-slip occurred continuously, so it was unusable. The measurement results are shown in Table 1 above.

[0215] Comparative Example 2

[0216] A multilayer sheet having a sealing layer thickness of 50 μm and a base layer thickness of 650 μm (hereinafter also referred to as the "multilayer sheet of Comparative Example 2") was obtained in the same manner as in Example 1, except that polypropylene resin A (product name: Novatec (registered trademark) FY6, manufactured by Japan Polypropylene Corporation) was supplied via a hopper to the sealing layer extruder 303 so as to account for 95 mass% of the mass of the first resin composition, and petroleum resin (product name: Alcon (registered trademark) P90, manufactured by Arakawa Chemical Co., Ltd.) was supplied to the sealing layer extruder 303 so as to account for 5 mass% of the mass of the first resin composition.

[0217] The peel strength of the multilayer sheet of Comparative Example 2 obtained was measured by the same method as in Example 1. The multilayer sheet sealed with a lid at 120°C and stored at room temperature had a peel strength of 0.78 kgf / 15 mm, and the peel morphology was a mixture of cohesive failure on the sealant layer side of the lid and interfacial peeling as shown in Figure 6, which was rated C (unacceptable). Stick-slip occurred continuously, so it was unusable. The multilayer sheet sealed with a lid at 160°C and stored in a freezer had a peel strength of 1.30 kgf / 15 mm, and the peel morphology was a mixture of cohesive failure on the sealant layer side of the lid and interfacial peeling as shown in Figure 6, which was rated C (unacceptable). Stick-slip occurred continuously, so it was unusable. The measurement results are shown in Table 1 above. [Explanation of symbols]

[0218] 10 containers 11 Container body 12 Lid material 13 Opening 14 Flange section

Claims

1. Polypropylene resin, A container body formed from a resin composition including a resin having a polar functional group; A lid material joined to the container body so as to seal the opening of the container body; A container having

2. The container of claim 1 , wherein the polar functional group is an oxygen-containing group.

3. The container according to claim 1, wherein the content of the polypropylene resin is 30 to 99 mass% relative to the mass of the resin composition.

4. The container according to claim 1, wherein the content of the resin containing a polar functional group is 1 to 70 mass % relative to the mass of the resin composition.

5. The container according to claim 1 , wherein the lid material has a sealant layer on a surface side to be joined to the resin composition.

6. The container of claim 5 , wherein the sealant layer comprises a hot melt composition.

7. The container of claim 6, wherein the hot melt composition comprises an ethylene-vinyl acetate copolymer resin.

8. The container according to claim 6, wherein when the container body and the lid material to which the hot melt composition is applied are bonded together and the lid material is peeled off from the container body at 25°C, cohesive failure occurs in the hot melt composition.

9. The container according to claim 6, wherein when the container body and the lid material to which the hot melt composition is applied are bonded together and the lid material is peeled off from the container body at 0°C, cohesive failure occurs in the hot melt composition.

10. Polypropylene resin, A sheet formed from a resin composition comprising: a resin having a polar functional group.

11. A base layer; A seal layer disposed on one surface side of the base layer; A sheet having The sealing layer is made of a polypropylene resin, and a resin including a polar functional group; The sheet, wherein the base layer is formed from a resin composition that is the same as or different from the first resin composition.

12. The sheet according to claim 10 or 11, wherein when a hot melt tape having a hot melt composition applied thereto is adhered to the sheet and the hot melt tape is peeled from the sheet at 25°C, the peel strength is 0.5 kgf / 15 mm or more.

13. The sheet according to claim 10 or 11, wherein when a hot melt tape having a hot melt composition applied thereto is adhered to the sheet and the hot melt tape is peeled from the sheet at 0°C, the peel strength is 0.5 kgf / 15 mm or more.

Citation Information

Patent Citations

  • Hot-melt composition, and lid material using the same

    JP2017149850A